Analisis Bauran Pemasaran Dalam Kaitannya Dengan Kepuasan Konsumen Dan Pengaruhnya Terhadap Keputusan Pembelian (Studi Kasus Penjualan Mebel Pada PT Multi Manunggal) - ., Sujana; Setiawan, Mardy (LPPM Institut Bisnis dan Informatika Kesatuan, 2016)
A Company’s main objective when running a business is to achieve the highest possible profit and sales and to develop markets all circles by performing campaigns and provide attractive offers to the consumer that the products sold by the company attract attention from consumers and companies acquire more consumers. If the company able to deliver what consumers want and making consumers satisfied with products that are produced by the company, then consumers will always buy the products that are sold by the company. The purpose of this research is to know how to influence the marketing mix to the satisfaction of the customer, to find out how the marketing mix of influences purchasing decisions, and to find out how the influence of customer satisfaction on purchasing decisions. As for the marketing mix variables, consumer satisfaction, and purchasing decisions will be identified and quantified the extent of the influence of these variables. The evaluation results in this study show that purchasing decisions on PT Multi Manunggal furniture can be influenced by the marketing mix and customer satisfaction by way of perfecting all activities such as good skills, knowledge, and expertise as well as discipline which are enforced programmatically by the company, to achieve optimal results. As for the marketing focused by PT Multi Manunggal, marketing mix of quality will be effecting positively the purchasing decisions and consumer satisfaction on an ongoing basis.